Synergistic leaching agent and method for recycling and regenerating positive electrode material of waste lithium ion battery
Through the synergistic leaching agent of inorganic acid solution and the compound of formula 1, the SEI and lattice structure of the cathode material of waste lithium-ion battery is improved, the leaching efficiency and effect are improved, and the material performance is improved through pH regulation and sintering treatment, solving the existing technology The problems of low leaching efficiency and poor material performance.
Patent Information
- Application Number
- CN202411171991.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-13
AI Technical Summary
The leaching efficiency of the positive electrode materials of existing waste lithium-ion batteries is low, requires high temperature and long time, and the electrochemical performance of the recycled materials needs to be improved.
The synergistic leaching agent of an inorganic acid solution and a specific compound of formula 1 is used to synergistically break through the surface SEI and lattice structure of the positive electrode material, which significantly improves the leaching efficiency and effect, and improves the material performance by optimizing the pH regulation and sintering treatment of the leaching solution.
Under mild conditions, more than 99% of valuable elements are efficiently leaching, reducing the difficulty of recycling the leaching liquid and improving the electrochemical properties of the regenerated positive electrode active material.
Smart Images

Figure CN119120936A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery waste recycling, and specifically relates to the field of waste lithium battery material recycling. Background Art
[0002] With the vigorous development of the new energy vehicle industry, a large number of power lithium-ion batteries are about to be retired. Waste lithium-ion batteries contain a large number of valuable metal elements. If they are not recycled, it will not only cause a large amount of resource waste but also cause serious environmental pollution. At present, pyrometallurgy and hydrometallurgy are the main methods for treating waste lithium-ion batteries. Compared with pyrometallurgical processes, relatively mild reaction conditions, simple processing technology and high recovery rate have become the main advantages of hydrometallurgical treatment.
[0003] Hydrometallurgical treatment methods mainly include acid leaching, alkali leaching, water leaching and other methods, among which acid leaching is the mainstream hydrometallurgical method. However, for acid leaching, it is difficult to effectively break through the physical and chemical structure of the surface of waste batteries by simply using inorganic acids, and it is difficult to obtain ideal leaching effects. Therefore, the industry often adopts a hydrogen peroxide-acid combined leaching solution.
[0004] For example, Chinese patent CN116495787A discloses a manganese-based composite prepared from waste lithium batteries and its preparation method, which specifically records the use of acidic solution and hydrogen peroxide to acid-leach the positive active material after heat treatment. For another example, Chinese patent document with publication number CN116722253A discloses a polar material leaching method and device for retired ternary lithium batteries, which specifically records the use of phosphoric acid and hydrogen peroxide leaching reagents to leach the clean polar material to obtain a metal salt solution containing Ni ions, Co ions, Mn ions and Li ions. For another example, Chinese patent document with publication number CN115057483A discloses a method for recovering high-nickel ternary battery positive electrode materials to prepare layered metal hydroxides, which specifically records the leaching of the high-nickel ternary positive electrode materials through inorganic acid solutions and hydrogen peroxide, and adjusting the pH value to 5-5.5 to obtain a leachate.
[0005] In summary, although the existing hydrogen peroxide-acid combined leaching method can achieve good leaching effects, it requires the use of explosive hydrogen peroxide, and the process safety is not ideal. In addition, the leaching efficiency needs to be improved. For example, most of them require a temperature above 50°C and a leaching time of more than 1 hour to obtain an ideal leaching effect. In addition, the regeneration of the leachate obtained by the existing leaching process is difficult, and the performance of the directly regenerated material needs to be improved. Summary of the invention
[0006] In view of the problems faced by the existing recycling of positive electrodes of waste lithium-ion batteries, the purpose of the present invention is to provide a method for leaching positive electrode materials of waste lithium-ion batteries, aiming to improve the leaching efficiency and effect.
[0007] The second object of the present invention is to provide a method for regenerating waste lithium-ion battery positive electrode materials, aiming to utilize waste positive electrode materials to regenerate high-performance positive electrode active materials.
[0008] Due to long-term circulation, the surface of the waste positive electrode material forms a dense SEI. In addition, its lattice stability is relatively high, and it is difficult to efficiently break through its physical and chemical structure by directly using a simple inorganic acid. Even with the use of hydrogen peroxide, its leaching efficiency is not ideal. In view of this problem, the present invention has been studied in depth and provides the following solutions:
[0009] A synergistic leaching agent for recovering valuable elements from waste lithium-ion battery positive electrode materials, comprising an inorganic acid solution and a compound of formula 1;
[0010]
[0011] The innovative research of the present invention shows that the combination of the structure of Formula 1 and the inorganic acid can unexpectedly effectively break through the SEI and lattice structure on the surface of the positive electrode material, and can significantly optimize the leaching efficiency and effect of the waste positive electrode material. For example, more than 99% of the valuable elements can be efficiently leached at a leaching temperature below 50°C and within 30 minutes. In addition, the treatment method described in the present invention also helps to reduce the difficulty of recycling the leachate, and helps to optimize the microscopic physical and chemical characteristics of the recycled material, and helps to improve the electrochemical properties of the regenerated material.
[0012] In the present invention, the inorganic acid is at least one of hydrochloric acid and sulfuric acid.
[0013] In the present invention, the molar concentration of the inorganic acid solution is 0.5-3M, and can be further 1-2M in consideration of effect and cost. The concentration of the compound of formula 1 is 0.5-5g / L, and can be further 1-3g / L in consideration of cost and effect.
[0014] In the present invention, the inorganic acid solution and the compound of formula 1 exist independently of each other before leaching, or exist in the form of a mixed solution.
[0015] The present invention also provides a leaching method for recovering valuable elements from waste lithium-ion battery positive electrode materials, wherein the waste lithium-ion battery positive electrode materials and the components in the synergistic leaching agent are mixed in any order for leaching, followed by solid-liquid separation to obtain a leachate enriched with valuable elements.
[0016] In the present invention, considering the market processing needs, the valuable elements in the waste positive electrode material may include lithium and at least one transition metal element of nickel, cobalt and manganese.
[0017] For example, it can be obtained by disassembling, stripping and separating at least one of waste lithium cobalt oxide batteries, waste lithium nickel oxide batteries, waste lithium manganese oxide batteries, waste nickel cobalt batteries and waste nickel cobalt manganese batteries through conventional means.
[0018] In the present invention, the inorganic acid solution and the compound of formula 1 can be stirred and aged in advance, and then mixed with the waste lithium-ion battery positive electrode material for acid leaching.
[0019] The aging temperature is, for example, 20 to 40° C., and the aging time is, for example, 20 to 60 minutes.
[0020] The research of the present invention shows that the adoption of this preferred scheme can further optimize the physicochemical reaction between Formula 1 and the inorganic acid, and can further enhance the synergistic efficiency and effect on the SEI and lattice structure of the waste positive electrode material.
[0021] In the present invention, thanks to the use of the combined leaching agent, an excellent leaching effect can be obtained under mild conditions. For example, the liquid-solid ratio in the leaching stage is 10-30 Ml / g.
[0022] Preferably, the temperature in the leaching stage is 15 to 45°C, further can be 20 to 40°C, further can be room temperature (e.g., 25 to 35°C);
[0023] Preferably, the leaching time is less than 30 minutes, and further preferably 10 to 20 minutes.
[0024] The present invention also provides a method for regenerating waste lithium-ion battery positive electrode materials, which comprises adopting the leaching method of the present invention to obtain a leachate, and then pre-regulating the pH of the leachate to 3.5-4.5, and then performing solid-liquid separation to obtain a first-stage purified liquid; then regulating the pH of the first-stage purified liquid to 10-12, and then performing solid-liquid separation to obtain a transition metal precursor and a lithium liquid; and adding a lithium precipitator to the lithium liquid to obtain a lithium precipitate;
[0025] The transition metal precursor and lithium precipitate are sintered to obtain a regenerated positive electrode active material.
[0026] In the present invention, thanks to the optimized leaching process, it not only helps to improve the leaching efficiency and effect of valuable elements, but also helps to reduce the difficulty of leaching valuable elements in the leachate, and helps to optimize its microstructure, which can further improve the performance of the regenerated positive electrode active material.
[0027] In the present invention, the pH regulator used to regulate the pH of the extract and the first-stage essence is a mixture of sodium hydroxide and ammonia water;
[0028] Preferably, the lithium precipitating agent is sodium carbonate;
[0029] Preferably, the calcination temperature is 700-900°C;
[0030] Preferably, the calcination time is 5 to 15 hours.
[0031] Beneficial Effects
[0032] The present invention innovatively combines the structure of Formula 1 with an inorganic acid, which can unexpectedly and effectively break through the SEI and lattice structure on the surface of the positive electrode material, and can significantly optimize the leaching efficiency and effect of the waste positive electrode material. In addition, the treatment method described in the present invention also helps to reduce the difficulty of recycling the leachate, and helps to optimize the microscopic physical and chemical characteristics of the recycled material, and helps to improve the electrochemical performance of the regenerated material. DETAILED DESCRIPTION
[0033] The present invention will be further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0034] The waste lithium ion battery positive electrode material of the present invention is a positive electrode material obtained by disassembling and stripping waste batteries. The stripping method can be well known in the industry. For example, waste lithium ion batteries are discharged, disassembled, and stripped (such as organic solvent NMP stripping) to obtain waste positive electrode powder. In the present invention, considering the simplicity of the process, the waste lithium ion battery positive electrode material is also allowed to contain at least one of a conductive agent, a binder, and an electrolyte.
[0035] In the present invention, there is no special requirement for the content of the positive electrode material of waste lithium-ion batteries. Considering the economic efficiency of the process, the content of the active material is preferably above 50wt.%, more preferably above 80wt.%, and further preferably 80-95wt.%.
[0036] Example 1
[0037] Step (1) stripping: placing a waste power nickel cobalt lithium manganese oxide (molar ratio Ni:Co:Mn is 0.9-1.1:0.9-1.1:1) battery into 2 mol / L salt water for 30 h of discharge treatment, drying the discharged battery at 85°C, disassembling and separating the positive electrode sheet and the negative electrode sheet, soaking the positive electrode sheet in N-methylpyrrolidone, separating the current collector in the electrode sheet, filtering, washing and drying to obtain waste positive electrode powder;
[0038] Step (2) leaching: pre-mix the waste positive electrode powder and Formula 1, then add 1M H2SO4 to mix and leach at 25°C for 15 minutes. The liquid-to-solid ratio in the leaching stage is 15 ml / g. The concentration of Formula 1 in the solution at the beginning of the leaching is 2 g / L (that is, the amount of Formula 1 and sulfuric acid solution involved is 2 g / L). After the leaching treatment, the solid and liquid are separated to obtain a solution rich in valuable metal ions (lithium, nickel, cobalt and manganese ions in this case).
[0039] The leaching rates of each valuable metal are Ni 98.8%, Co 98.3%, Mn 99.2%, and Li 99.3%.
[0040] Step (3) stepwise precipitation: for the above solution, add NaOH-NH3·H2O to adjust the pH to 4 to remove iron and aluminum, and adjust the ratio of nickel, cobalt and manganese in the filtrate obtained after filtration to 1:1:1, then add NaOH-NH3·H2O to adjust the pH to 11 to precipitate nickel, cobalt and manganese, and add Na2CO3 to the filtrate obtained after filtration to evaporate and crystallize to obtain Li2CO3.
[0041] Step (4) regeneration: After the obtained nickel-cobalt-manganese coprecipitate and Li2CO3 are evenly mixed, the molar ratio of lithium to transition metal is controlled to be 1.05:1, and then annealed at 800°C for 10 hours to obtain a regenerated positive electrode active material.
[0042] The regenerated active material (active material), PVDF, and conductive carbon black are mixed in a weight ratio of 8:1:1 to form a slurry and coated on the positive electrode current collector, and then dried to obtain a positive electrode to be tested;
[0043] In a glove box, 1M LiPF6 was used as the electrolyte (EC:DEC:EMC=1:1:1), and the separator was Celgard2400 polypropylene film. Lithium was used as the counter electrode, and the obtained regenerated positive electrode was used as the working electrode to assemble a CR2025 battery. The regenerated positive electrode at a rate of 1C at room temperature showed a reversible capacity of 185 mAh / g.
[0044] Example 2
[0045] Compared with Example 1, the only difference is that lithium nickel cobalt manganese oxide is replaced by lithium cobalt oxide, and other operations and parameters are the same as Example 1.
[0046] In step (2), the leaching rate of each valuable metal is Co99.0% and Li99.5%. In the glove box, 1M LiPF6 is used as the electrolyte (EC:DEC:EMC=1:1:1), and the diaphragm is Celgard2400 polypropylene film. With lithium as the counter electrode, the positive electrode regenerated at a rate of 1C at room temperature shows a reversible capacity of 148 mAh / g.
[0047] Example 3
[0048] Compared with Example 1, the only difference is that the positive electrode material is replaced with lithium manganese oxide, and the other operations and parameters are the same as Example 1.
[0049] In step (2), the leaching rates of each valuable metal are Mn 99.8% and Li 99.7%.
[0050] In the glove box, 1M LiPF6 was used as the electrolyte (EC:DEC:EMC=1:1:1), and the separator was Celgard 2400 polypropylene membrane. With lithium as the counter electrode, the positive electrode showed a reversible capacity of 138 mAh / g at a rate of 1C at room temperature.
[0051] Example 4
[0052] Compared with Example 1, the only difference is that the leaching temperature is changed to 35° C., and other operations and parameters are the same as Example 1.
[0053] In step (4), the leaching rate of each valuable metal is Ni99.6%, Co99.5%, Mn99.7%, Li99.8%. In the glove box, 1M LiPF6 is used as the electrolyte (EC:DEC:EMC=1:1:1), and the diaphragm is Celgard2400 polypropylene film. With lithium as the counter electrode, the positive electrode regenerated at a rate of 1C at room temperature shows a reversible capacity of 190 mAh / g.
[0054] Example 5
[0055] Compared with Example 1, the only difference is that H2SO4 is replaced by HCl, and other operations and parameters are the same as Example 1.
[0056] In step (4), the leaching rate of each valuable metal is Ni 99.1%, Co 99.7%, Mn 99.3%, and Li 99.8%. In the glove box, 1M LiPF6 is used as the electrolyte (EC:DEC:EMC=1:1:1), and the diaphragm is Celgard2400 polypropylene film. With lithium as the counter electrode, the positive electrode regenerated at a rate of 1C at room temperature shows a reversible capacity of 189 mAh / g.
[0057] Example 6
[0058] Compared with Example 1, the only difference is that the concentration of Formula 1 in the solution at the start of leaching is 3 g / L, and other operations and parameters are the same as Example 1.
[0059] In step (2), the leaching rate of each valuable metal is Ni 99.3%, Co 99.8%, Mn 99.5%, and Li 99.9%. In the glove box, 1M LiPF6 is used as the electrolyte (EC:DEC:EMC=1:1:1), and the diaphragm is Celgard2400 polypropylene film. With lithium as the counter electrode, the positive electrode regenerated at a rate of 1C at room temperature shows a reversible capacity of 193 mAh / g.
[0060] Example 7
[0061] Compared with Example 1, the only difference is that the H2SO4 concentration is changed to 2M, the liquid-to-solid ratio in the leaching stage is 10ml / g, and the other operations and parameters are the same as Example 1.
[0062] In step (2), the leaching rate of each valuable metal is Ni99.2%, Co99.8%, Mn99.6%, Li99.8%. In the glove box, 1M LiPF6 is used as the electrolyte (EC:DEC:EMC=1:1:1), and the diaphragm is Celgard2400 polypropylene film. With lithium as the counter electrode, the positive electrode regenerated at a rate of 1C at room temperature shows a reversible capacity of 191 mAh / g.
[0063] Example 8
[0064] Compared with Example 1, the only difference is that the leaching time is changed to 10 minutes, and the other operations and parameters are the same as Example 1.
[0065] In step (2), the leaching rate of each valuable metal is Ni 99.0%, Co 99.6%, Mn 99.4%, Li 99.6%. In the glove box, 1M LiPF6 is used as the electrolyte (EC:DEC:EMC=1:1:1), and the diaphragm is Celgard2400 polypropylene film. With lithium as the counter electrode, the positive electrode regenerated at a rate of 1C at room temperature shows a reversible capacity of 188 mAh / g.
[0066] Example 9
[0067] Compared with Example 1, the only difference is that Formula 1 and H2SO4 are stirred and aged at room temperature for 1 hour in advance, and then mixed with waste positive electrode powder for in-and-out treatment. Other operations and parameters are the same as Example 1.
[0068] In step (2), the leaching rate of each valuable metal is Ni99.9%, Co99.9%, Mn99.9%, Li99.9%. In the glove box, 1M LiPF6 is used as the electrolyte (EC:DEC:EMC=1:1:1), and the diaphragm is Celgard2400 polypropylene film. With lithium as the counter electrode, the positive electrode regenerated at a rate of 1C at room temperature shows a reversible capacity of 195 mAh / g.
[0069] Comparative Example 1
[0070] Compared with Example 1, the only difference is that Formula 1 is not added. Other operations and parameters are the same as in Example 1.
[0071] The leaching rates of the valuable metals in step (2) are Ni 54.4%, Co 58.2%, Mn 58.5%, and Li 69.7%.
[0072] In the glove box, 1M LiPF6 was used as the electrolyte (EC:DEC:EMC=1:1:1), and the separator was Celgard 2400 polypropylene membrane. With lithium as the counter electrode, the positive electrode showed a reversible capacity of 134 mAh / g at a rate of 1C at room temperature.
[0073] Comparative Example 2
[0074] Compared with Example 1, the only difference is that an equal weight of hydrogen peroxide is used to replace Formula 1. Other operations and parameters are the same as in Example 1.
[0075] In step (2), the leaching rates of each valuable metal are Ni80.3%, Co82.4%, Mn78.6%, and Li86.4%. In the glove box, 1M LiPF6 is used as the electrolyte (EC:DEC:EMC=1:1:1), and the diaphragm is Celgard2400 polypropylene film. With lithium as the counter electrode, the positive electrode regenerated at a rate of 1C at room temperature shows a reversible capacity of 169 mAh / g.
[0076] Comparative Example 3
[0077] Compared with Example 1, the only difference is that the same weight is used Replace Formula 1. Other operations and parameters are the same as in Example 1.
[0078] In step (2), the leaching rates of each valuable metal are Ni 52.6%, Co 55.7%, Mn 58.1%, and Li 66.7%. In the glove box, 1M LiPF6 is used as the electrolyte (EC:DEC:EMC=1:1:1), and the diaphragm is Celgard2400 polypropylene film. With lithium as the counter electrode, the positive electrode regenerated at a rate of 1C at room temperature shows a reversible capacity of 135 mAh / g.
[0079] Comparative Example 4
[0080] Compared with Example 1, the only difference is that the same weight is used Replace Formula 1. Other operations and parameters are the same as in Example 1.
[0081] In step (2), the leaching rates of each valuable metal are Ni72.8%, Co73.7%, Mn79.2%, and Li83.8%. In the glove box, 1M LiPF6 is used as the electrolyte (EC:DEC:EMC=1:1:1), and the diaphragm is Celgard2400 polypropylene film. With lithium as the counter electrode, the positive electrode regenerated at a rate of 1C at room temperature shows a reversible capacity of 153 mAh / g.
Claims
1. A synergistic leaching agent for recovering valuable elements from waste lithium-ion battery cathode materials, characterized in that: It includes an inorganic acid solution and a compound of formula 1; 2. The synergistic leaching agent according to claim 1, characterized in that The inorganic acid is at least one of hydrochloric acid and sulfuric acid.
3. The synergistic leaching agent according to claim 1 or 2, characterized in that The molar concentration of the inorganic acid solution is 0.5 to 3 M, and the concentration of the compound of formula 1 is 0.5 to 5 g / L.
4. The synergistic leaching agent according to any one of claims 1 to 3, characterized in that The inorganic acid solution and the compound of formula 1 exist independently of each other before leaching, or exist in the form of a mixed solution.
5. A leaching method for recovering valuable elements from waste lithium-ion battery positive electrode materials, characterized in that: The waste lithium-ion battery positive electrode material and the components of the synergistic leaching agent according to any one of claims 1 to 4 are mixed in any order for leaching, followed by solid-liquid separation to obtain a leachate enriched with valuable elements.
6. The leaching method according to claim 5, characterized in that The valuable elements include lithium and at least one transition metal element selected from nickel, cobalt and manganese.
7. The leaching method according to claim 5 or 6, characterized in that: The inorganic acid solution and the compound of formula 1 are stirred and aged in advance, and then mixed with the waste lithium-ion battery positive electrode material for acid leaching.
8. The leaching method according to any one of claims 5 to 7, characterized in that: The liquid-to-solid ratio in the leaching stage is 10-30 Ml / g; Preferably, the temperature in the leaching stage is 15-45°C; Preferably, the leaching time is less than 30 minutes, and further preferably 10 to 20 minutes.
9. A method for regenerating waste lithium-ion battery positive electrode materials, characterized in that: The leaching solution is obtained by the leaching method according to any one of claims 5 to 8, and the pH of the leaching solution is adjusted to 3.5 to 4.5 in advance, followed by solid-liquid separation to obtain a first-stage purified solution; The pH of the first stage purification liquid is then adjusted to 10-12, followed by solid-liquid separation to obtain a transition metal precursor and a lithium liquid; Adding a lithium precipitating agent to the lithium solution to obtain lithium precipitate; The transition metal precursor and lithium precipitate are sintered to obtain a regenerated positive electrode active material.
10. The method for regenerating the positive electrode material of waste lithium-ion batteries according to claim 9, characterized in that: The pH regulator used to regulate the pH of the extract and the first-stage essence is a mixture of sodium hydroxide and ammonia water; Preferably, the lithium precipitating agent is sodium carbonate; Preferably, the calcination temperature is 700-900°C; Preferably, the calcination time is 5 to 15 hours.
